2019
DOI: 10.1073/pnas.1815034116
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic targeting of HER2–CB 2 R heteromers in HER2-positive breast cancer

Abstract: Although human epidermal growth factor receptor 2 (HER2)-targeted therapies have dramatically improved the clinical outcome of HER2-positive breast cancer patients, innate and acquired resistance remains an important clinical challenge. New therapeutic approaches and diagnostic tools for identification, stratification, and treatment of patients at higher risk of resistance and recurrence are therefore warranted. Here, we unveil a mechanism controlling the oncogenic activity of HER2: heteromerization with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 46 publications
(58 reference statements)
1
44
0
Order By: Relevance
“…This could explain why the two cannabinoid combinations containing THC had the lowest IC values amongst the combinations tested ( Table 2 ). In addition, the binding of cannabinoids to the CB 2 receptor disrupts the HER2/CB 2 heterodimer formation, inhibiting proliferation via the PI3K/Akt pathway [ 41 ]. Since the C6 combination comprises four cannabinoids that can all bind to the CB2 receptor [ 42 ], their anti-proliferative effects in the MCF-7 cells would be amplified when cannabinoids are combined.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why the two cannabinoid combinations containing THC had the lowest IC values amongst the combinations tested ( Table 2 ). In addition, the binding of cannabinoids to the CB 2 receptor disrupts the HER2/CB 2 heterodimer formation, inhibiting proliferation via the PI3K/Akt pathway [ 41 ]. Since the C6 combination comprises four cannabinoids that can all bind to the CB2 receptor [ 42 ], their anti-proliferative effects in the MCF-7 cells would be amplified when cannabinoids are combined.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Blasco-Benito et al observed that HER2 interacts with CB2 receptors in breast cancer cells and the expression of these heteromers correlates with poor patient prognosis. The cannabinoid ∆9-THC disrupted HER2-CB2R complexes by selectively binding to CB2R, which led to the inactivation and degradation of HER2 through disruption of HER2-HER2 homodimers promoting antitumoral responses both in vitro and in vivo, which may constitute a new strategy to treat HER2+ breast tumors [84].…”
Section: Breast and Prostate Cancersmentioning
confidence: 99%
“…High CB1R expression correlates with poor prognosis in different type of cancers including prostate, pancreatic, colorectal, and ovarian cancer (Michalski et al, 2008;Cipriano et al, 2013;Jung et al, 2013;Messalli et al, 2014); while high CB2R expression correlated to poor prognosis in HER2positive breast cancer (Blasco-Benito et al, 2019). Endocannabinoids such as AEA and 2-AG were found upregulated in different tumors (colorectal carcinomas) compared to healthy subjects (Pyszniak et al, 2016).Despite these changes there have been variable mechanisms suggested for these endocannabinoids in terms of their antitumorigenic activity.…”
Section: Editorial On the Research Topicmentioning
confidence: 99%